English Learning that Fosters Positive Attitudes - Gunawan, Y.B. (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2014)
This article discusses the integration of English teaching and attitude components. In the new school curriculum the attitude or affective domain components are considered very important as we can see in the Core Competence and Basic Competence. The English teacher should be able to teach English while paying attention to the attitude components. This article aims to show that the two aspects can be done together. The assumption taken is that while teaching English, the teacher also develops the students affective domain/deals with the learners attitude. What remains to be done is that the English teacher should be able to identify his/her theoretical orientation that he/she has with regard to language, language learning, and educational cultural viewpoints. One of these viewpoints language learning is further elaborated in H.D. Browns second language learning principles. With these major concepts and principles the English teacher is expected to be able to integrate the English teaching-learning process with the affective-domain related process.